Comorbid case of IgG4-related disease and primary Sjögren's syndrome. Issue 3 (May 2015) - Nakashima, Yoshikazu; Nakamura, Hideki; Horai, Yoshiro; Hayashi, Tomayoshi; Takagi, Yukinori; Nakamura, Takashi; Kawakami, Atsushi
Abstract A 63-year-old man with enlargement of the bilateral submandibular glands visited with elevated serum IgG4. A biopsy specimen showed plasma cell infiltration with more than 50% IgG4/IgG staining, suggesting the existence of IgG4-related disease (IgG4-RD). Positive anti-SS-A/Ro antibody and the labial salivary gland's biopsy suggested existence of primary Sjögren's syndrome (pSS). Administration of glucocorticoid improved the serum IgG4 level while reducing the submandibular gland lesions. Positive TUNEL staining suggested the coexistence of IgG4-RD and pSS.